Sonographic Evaluation of the Distal Iliopsoas Tendon Using a New Approach. (1st November 2014) - Balius, Ramon; Pedret, Carles; Blasi, Marc; Miguel, Maribel; Vallejo, Beatriz; Margalet, Eric; Bong, David A.; Martinoli, Carlo
Abstract : Sonography of the iliopsoas tendon plays an important role in the diagnosis and preoperative and postoperative management for the increasing number of patients under consideration for arthroscopically guided hip interventions such as iliopsoas tenotomy in a variety of conditions, including arthropathy, periarticular calcifications, and cam‐type deformities of the femoral head. The ability to visualize the iliopsoas tendon pre‐operatively can be helpful diagnostically in patients presenting with hip pain and can aid in planning surgery, while evaluating the tendon postoperatively is important in the assessment of causes of postoperative pain and other potential complications. We present a novel technique for visualizing the distal iliopsoas tendon complex in the longitudinal axis at its insertion on the lesser trochanter on sonography.